Student Attitudes Towards Jordanian Universities - Reality and Expectations - Qasem, Asma Maher (Journal of Educational and Psychological Sciences, 2025)
This study aimed to identify students’ attitudes towards teaching in Jordanian universities, both in its current state and in their desired expectations, with the goal of uncovering students’ needs and expectations regarding instruction. A qualitative research approach was employed. The study sample comprised (28) students, selected purposively through a shared WhatsApp group. A link to the questionnaire was distributed within the group and via Messenger for those not using WhatsApp. The sample included (13) male students and (15) female students, of whom (16) were from public universities and (12) from private universities, all at the undergraduate level. The study relied on focus groups answering open-ended questions on social media to reveal students’ needs and expectations, followed by analysis and re-presentation to the participants for discussion, along with proposed suggestions. The study’s findings revealed that the most significant issues in teaching within higher education are: the use of lecturing and note-taking as the primary teaching method; a high volume of theoretical material compared to practical application, coupled with insufficient field training; reliance on external educational institutions to support course content; a lack of technological preparedness among faculty members; assessment methods that do not account for individual differences, have unclear criteria, and fail to evaluate practical skills; and the view that technology is beneficial for teaching when used as a supplement, not a replacement. Based on these results, the researcher recommended the need for more extensive practical application and field experience, for faculty members to undergo assessments to ensure their readiness for advanced university teaching, and for the scientific and research-based modernization of teaching methods. The study also suggested future research on the topic.